Three-dimensional multi-recognition flexible wearable sensor via graphene aerogel printing. Issue 73 (17th August 2016) - An, Boxing; Ma, Ying; Li, Wenbo; Su, Meng; Li, Fengyu; Song, Yanlin
Abstract : Multi-response, multi-function and high integration are the critical pursuits of advanced electronic wearable sensors. Abstract : Multi-response, multi-function and high integration are the critical pursuits of advanced electronic wearable sensors. Graphene aerogel endows a three-dimensional (3D) deformation morphology with excellent flexible wearable electronics of sheeted graphene. Here we report the fabrication of a neat graphene aerogel with micro extrusion printing to electronic sensor devices with a 3D nanostructure. The printed neat graphene patterns have excellent conductivity and the controllable 3D nanostructure of graphene aerogel contributes multi-dimensional deformation responses, which are appropriately suitable for the multi-recognition flexible wearable electric sensor. With complicated movement perception, the printed graphene aerogel sensors run the remarkable gesture language analysis for a deaf–mute communication auxiliary device or gesture manipulation apparatuses.